(NwOL[EBNYJ SUNDUK (B/s - (NcYMBAL@K(B, (NnATALXQ(B.s; (NfLORQK(B, )Qæ.s)E ((N~ERNOWCY (B:s (NqWORSKIJ s(B. (Nn(B.,s, 2021)
"(NwOL[EBNYJ SUNDUK(B" - (NCE ZB)QÆRKA NEZWI^AJNIH ÆSTORÆJ(B, (NMEDATIWNIH KAZOK(B. (NwAVLIWO TÆLXKI WÆDKRITI SERCE Æ DOZWOLITI SOBÆ ZUPINITI ^AS(B, (NTRÆ[KI ROZSLABITISX(B. (NcÆÃ@ ATMOSFERO@ OPOWITA KOVNA ÆZ ZÆBRANIH KAZOK(B.s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (Nl)QÆTERATURA uKRAÇNIs)E -- (NpROZAs -- (NrOS)QÆJSXKOMOWNA (B-- (NdITQ^A(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E